2006
DOI: 10.1002/humu.9457
|View full text |Cite
|
Sign up to set email alerts
|

Unique substitution ofCHEK2 andTP53 mutations implicated in primary prostate tumors and cancer cell lines

Abstract: Genetic defects in CHEK2 and TP53 have been implicated in prostate cancer development. However, the interaction of these two genes in prostate cancer tumorigenesis has not been investigated. We previously described 11 CHEK2 mutations in a group of 84 primary prostate tumors. In this report, we screened the same group of tumors for TP53 mutations and revealed nine somatic and two germline mutations. One germline TP53 mutation (c.408A>T/p.Gln136His) and two somatic mutations (c.1022T>G/p.Phe341Cys and c.108-109i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
(23 reference statements)
1
15
0
Order By: Relevance
“…DU145 cells harbor mutations of codon 223 (CCT to CTT, Pro to Leu) and codon 274 (GTT to TTT, Val to Phe), also resulting in abnormal TP53 proteins (23,47). Although LNCaP cells express wild-type TP53, it harbors mutation of CHK2 at codon 1160 (C to A, Thr to Asn), leading to deficit of TP53 protein phosphorylation and activation (48). In prostate cancer tissue, about half harbor TP53 abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…DU145 cells harbor mutations of codon 223 (CCT to CTT, Pro to Leu) and codon 274 (GTT to TTT, Val to Phe), also resulting in abnormal TP53 proteins (23,47). Although LNCaP cells express wild-type TP53, it harbors mutation of CHK2 at codon 1160 (C to A, Thr to Asn), leading to deficit of TP53 protein phosphorylation and activation (48). In prostate cancer tissue, about half harbor TP53 abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…A number of candidate genes have been reported that harbor somatic mutations in localized prostate cancer, including AR, TP53, KLF6, EPHB2, CHEK2, ZFHX3 (formerly known as ATBF1), and NCOA2 (Newmark et al 1992;Gottlieb et al 2004;Huusko et al 2004;Sun et al 2005;Dong 2006;Zheng et al 2006;Agell et al 2008;Taylor et al 2010). However, there are limited reports of somatic coding mutations in metastatic tumors.…”
mentioning
confidence: 99%
“…52 It has also been reported that mutations in TP53 and CHEK2, a gene activated in response to various DNA-damaging agents, could be mutually exclusive in 25% of prostate tumors. 53 From all these studies, it is obvious that, although KLF6 and TP53 are important in controlling the cell cycle, their involvement in the pathogenesis of prostate cancer is still controversial and uncertain. Thus, the main goal of the present study has been to elucidate the real frequency of KLF6 and TP53 mutations in a large group of prostate cancer samples classified by stage and Gleason grade and performing more than one round of PCR and sequencing, in order to avoid artifactual mutations and other methodological problems often encountered in formalin-fixed, paraffin-embedded (FFPE) samples.…”
mentioning
confidence: 99%